PERCEPTIONS OF MSME ACTORS TOWARDS DISCLOSURE OF SUSTAINABILITY REPORTS (CASE STUDY ON MSME BONTOLOE, TAKALAR DISTRICT) - Nadhirah Nagu; Anas Iswanto Anwar; Mursalim Nohong; Amiruddin Amiruddin; Haeriah Hakim; Muhammad Rifai; Audy Alifia Rudy (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to examine differences in the perceptions of MSME actors on sustainability reporting disclosures. This difference in perception will be tested on environmentally sensitive MSMEs and non-environmentally sensitive MSMEs. Differences in the perceptions of MSME actors will then be tested on the compliance aspect; aspects of understanding sustainability; sustainable corporate governance aspects; aspects of political, environmental and social sustainability performance; and aspects of the economic performance of SMEs. The research population is the research sample used, consisting of 120 MSME actors consisting of 10 service MSMEs and 110 non-service MSMEs. The research data was processed using SPSS 25. The results of the study showed that there were significant differences in aspects of sustainable understanding, aspects of political, environmental and social sustainability performance, and aspects of economic performance between environmentally sensitive MSMEs and non-environmentally sensitive MSMEs, but there were no differences significantly to the compliance aspect and sustainable corporate governance aspects.